Metallothionein I-II immunocytochemical reactivity in Binswanger's encephalopathy - Zambenedetti, Pamela; Schmitt, Horst Peter; Zatta, Paolo (Journal of Alzheimer's disease, 2002)
Binswanger's disease is a subacute form of hypertensive encephalopathy characterized by patchy-confluent myelin loss of the deep hemispheric white matter, associated with marked regressive changes of the oligodendrocytes and variable astroglial reaction. To understand the distribution and the specificity of astrocyte pathology in Binswanger's disease we quantified reactive and degenerating astrocytes in different regions of the deep and subcortical white matter and of the cerebral cortex. Sections of frontal, temporal, parietal, and occipital lobes of 12 histologically proven cases of Binswanger's disease were immunostained with antibodies to glial fibrillary protein (GFAP) and to metallothionein I and II (MT-I-II), markers which specifically identify normal and reactive astrocytes. Control tissues were from 6 elderly patients without neurological diseases. The brains of Binswanger's disease were characterized by few and lightly immunostained astrocytes in the deep white matter, but normal and reactive astrocytes, strongly immunoreactive for GFAP and MT-I-II, were prominent in the subcortical white matter and the cerebral cortex. However, the relative distribution of GFAP positive and MT-I-II positive astrocytes was significantly different between the cerebral cortex and the subcortical white matter, the MT-I-II positive astrocytes being more frequent in the cerebral cortex, and the GFAP positive astrocytes in the subcortical white matter (p < 0.02). The GFAP and MT-I-II expressions in subsets of reactive astrocytes in the cortico-subcortical layers together with regressive astroglial changes in the deep white matter suggest that the dynamic plasticity of astroglia is topographically and biochemically differentiated in vascular dementia of Binswanger type.